2020
DOI: 10.3389/fcell.2020.00649
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a TLR-Induced Four-lncRNA Signature as a Novel Prognostic Biomarker in Esophageal Carcinoma

Abstract: Long non-coding RNAs (lncRNAs) have emerged as key regulators of Toll-like receptor (TLR) signaling to control innate immunity, and this regulatory mechanism has recently been implicated in esophageal carcinoma (ESCA). However, a comprehensive analysis of TLR-induced lncRNAs and their roles in diagnosis and prognosis in ESCA is still lacking. In this study, we first investigated the precise relationship between lncRNA perturbations and alteration of TLR signaling by constructing the lncRNA-TLRs coexpression ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…For example, Liu et al found that MALAT1 may have an oncogenic function in PTC and may thus be a potential diagnostic marker for PTC [26]. In our research, a few of the DEirlncRNAs in the model, such as SMIM25, [27] LINC00900, [28] AC010980.2, [29] HAGLROS, and LINC01977 [30], have already been revealed to play roles in various cancers, especially TC, while others were found to be related to TC for the rst time. Nevertheless, it is necessary to validate whether this immune-related lncRNA model could be a helpful predictive indicator in TC.…”
Section: Discussionsupporting
confidence: 47%
“…For example, Liu et al found that MALAT1 may have an oncogenic function in PTC and may thus be a potential diagnostic marker for PTC [26]. In our research, a few of the DEirlncRNAs in the model, such as SMIM25, [27] LINC00900, [28] AC010980.2, [29] HAGLROS, and LINC01977 [30], have already been revealed to play roles in various cancers, especially TC, while others were found to be related to TC for the rst time. Nevertheless, it is necessary to validate whether this immune-related lncRNA model could be a helpful predictive indicator in TC.…”
Section: Discussionsupporting
confidence: 47%
“…To improve EC treatment, research on abnormally expressed genes in EC pathogenesis is of great importance [ 32 ]. Accumulating evidence confirmed that lncRNAs exert profound effects in EC pathogenesis and progression at molecular level [ 33 ]. For example, Chen et al disclosed that lncRNA CASC11 upregulated KLF6 to promote EC development [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need to identify key biomarkers that affect the outcome of BC. With future expansion of the database and multi-omics data, improved data mining algorithms can have an essential impact on tumor biology ( Angus et al, 2019 ; Nacev et al, 2019 ; Liu et al, 2020 ; Tabassum et al, 2020 ). Transcriptome profiling provided us with novel insights into assessing prognostic of the individual patient when combining the corresponding clinical information.…”
Section: Discussionmentioning
confidence: 99%